Characterization of subclinical diastolic dysfunction by cardiac magnetic resonance feature-tracking in adult survivors of non-Hodgkin lymphoma treated with anthracyclines - Barbosa, Maurício Fregonesi [UNESP]; Fusco, Daniéliso Renato [UNESP]; Gaiolla, Rafael Dezen [UNESP]; Werys, Konrad; Tanni, Suzana Erico [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Ribeiro, Sergio Marrone [UNESP]; Szarf, Gilberto (Springer Nature, 2021)
Background: The use of anthracycline-based chemotherapy is associated with the development of heart failure, even years after the end of treatment. Early detection of cardiac dysfunction could identify a high-risk subset of survivors who would eventually benefit from early intervention. Cardiac magnetic resonance feature-tracking (CMR-FT) analysis offers a practical and rapid method to calculate systolic and diastolic strains from routinely acquired cine images. While early changes in systolic function have been described, less data are available about late effects of chemotherapy in diastolic parameters by CMR-FT. The main goal of this study was to determine whether left ventricular (LV) early diastolic strain rates (GDSR-E) by CMR-FT are impaired in long-term adult survivors of non-Hodgkin lymphoma (NHL). Our secondary objective was to analyze associations between GDSR-E with cumulative anthracycline dose, systolic function parameters and myocardial tissue characteristics. Methods: This is a single center cross-sectional observational study of asymptomatic patients in remission of NHL who previously received anthracycline therapy. All participants underwent their CMR examination on a 3.0-T scanner, including cines, T2 mapping, T1 mapping and late gadolinium enhancement imaging. Derived myocardial extracellular volume fraction was obtained from pre- and post-contrast T1 maps. CMR-FT analysis was performed using Trufi Strain software. The data obtained were compared between anthracycline group and volunteers without cardiovascular disease or neoplasia. Results: A total of 18 adult survivors of NHL, 14 (77.8%) males, at mean age of 57.6 (± 14.7) years-old, were studied 88.2 (± 52.1) months after exposure to anthracycline therapy (median 400 mg/m2). Compared with controls, anthracycline group showed impaired LV global early diastolic circumferential strain rate (GCSR-E) [53.5%/s ± 19.3 vs 72.2%/s ± 26.7, p = 0.022], early diastolic longitudinal strain rate (GLSR-E) [40.4%/s ± 13.0 vs 55.9%/s ± 17.8, p = 0.006] and early diastolic radial strain rate (GRSR-E) [− 114.4%/s ± 37.1 vs − 170.5%/s ± 48.0, p < 0.001]. Impaired LV GCSR-E, GLSR-E and GRSR-E correlated with increased anthracycline dose and decreased systolic function. There were no correlations between GDSR-E and myocardial tissue characteristics. Conclusions: Left ventricular early diastolic strain rates by CMR-FT are impaired late after anthracycline chemotherapy in adult survivors of non-Hodgkin lymphoma.
Keywords: Cancer; Chemotherapy; Diastolic dysfunction; Feature-tracking; Strain